Fatigue life and fracture assessment of SA 333 Gr. 6 carbon steel straight pipes with circumferential crack - Murthy, A. Ramachandra; Vishnuvardhan, S.; Saravanan, M.; Kumar, Abhishek; Gandhi, P.; Singh, P. K. (Journal of Structural Engineering, 2024)
It is known that damage tolerant evaluation has primarily two objectives, namely, crack growth life and residual strength. In the present study, remaining life and residual strength evaluation of SA 333 Gr. 6 carbon steel straight pipes with circumferential part through crack under cyclic loading has been carried out. The study involves evaluation of accurate crack driving force, i.e., Stress Intensity Factor (SIF), crack growth and remaining life of cracked pipe. SIF has been evaluated for the cracked pipes using French RCC-MR and R6 approaches. Crack growth life has been evaluated using Paris law. The predicted crack growth life has been compared with the previous experimental results and found to be close to each other with maximum difference of 13%. Residual strength has been determined by using (i) plastic collapse condition with yield stress and flow stress (ii) fracture toughness criterion and (iii) remaining life approach. The residual strength obtained using plastic collapse condition with yield stress is lower compared to other approaches. The predicted remaining life and residual strength are useful for safe operation of power plant structures based on fitness for purpose requirements.